The Effect Of Traditional Herbal Medicine On The Fitness Level Of Swimming Athletes In Palopo City - Resky Resky; A. Heri Riswanto; Hajeni Hajeni; M. Iqbal Hasanuddin (STKIP Muhammadiyah Kuningan, 2023)
Traditional herbal medicine is a heritage used for treatment and health maintenance in Indonesia. One is to improve physical fitness with ginger, free-range chicken eggs, palm sugar and honey. The purpose of this study is to determine the effect of herbal medicine on the physical fitness level of swimming athletes in Palopo to discover if traditional herbal drinks affect physical fitness levels. This study uses an experimental method with a one-group pretest-posttest research design with the number of samples in this study are 15 athletes combined into one group. This research was conducted for 16 meetings. The analysis was carried out in the University of Muhammadiyah Palopo campus; the groups were combined into one and given treatment in the form of herbal drinks after carrying out pretest activities with a dose of 250 ml. To measure the final data of the fitness test after consuming the herbal drink, a posttest was carried out, which later became a comparison of whether there was an effect of the herbal drink on the level of physical fitness. The results of this research show an improvement in physical fitness by drinking traditional herbal medicine the Palopo Swimming athletes. Thus, there is a significant relationship between consuming conventional herbal medicine and Palopo swimming athletes' physical fitness.